Tomorrow, things will be different Qiu Zhijie's concept of keeping alive life through art. Issue 1 (2nd January 2017) - Hopfener, Birgit
Abstract: The paper examines Qiu Zhijie's multi-layered project A Suicidology of the Nanjing Yangtze River Bridge (since 2008) and asks what is at stake when art literally and metaphorically is assigned with life-saving functions. Based on the artist's assumption that today's social and political reality as well as its subjects are historically constructed the article conceives of the Nanjing Bridge as an embodiment of a historically constituted contemporary Chinese reality. Through close readings of the works as well as analyses of theoretical writings by Qiu Zhijie the article scrutinises the relationship Total Art assumes between the social and the aesthetic realm and examines the premises and strategies the artist adopts in order to produce socially and aesthetically effective art that keeps 'alive'.